Development of a self propelled pre- germinated direct paddy seeder - JAYAPRAKASH BABU K; Er. Manoj Mathew (Gudie) (Tavanur 2001 Kelappaji College of Agricultural Engineering and Technology)
the project was undertaken with the objective to study the metering characteristics of drums for pre-germinated paddy seeder with fixed ground wheel on seed drum shaft.
Development of a self propelled pre- germinated direct paddy seeder